THE PYGMALION EFFECT: HOW EXPECTATIONS INFLUENCE TEACHERS’ GRADING DECISION MAKING - Nisrina Nisrina (VISION, 2020)
This study investigated teachers’ expectation for students that lead to the choice of assessment types and the considered factors in grading decision making. Two teachers from different public senior high school were selected. The phenomenon where the positive teaching expectations deliberately lead to high student achievement (Pygmalion effect) is found in this study. The results show that positive teachers’ expectation for students will be reflected through their positive body language and give learning instruction more challenging for those who can fulfill their expectation i.e high achievement students. The expectations are dealing with students’ active participation the class and manner or attitude. Henceforth, teachers give more concern in applying informal assessment in grading students’ achievement in which process is more concerned instead of result. In addition, their expectations for students are used in considered factor in grading students’ achievement that is reflected in the report cards. Low achievement students could receive disadvantageous learning condition because of teachers’ expectation influencing their performance in a negative way, as grant their grade in report cards does not measure their real achievement.